(untitled) (SCHOOLAR: Social and Literature Study in Education, 2023)
The role of Islamic teachers is very important in shaping the character of a student in a madrasah school educational institution. The development of students’ morals in schools by Islamic Religious Education teachers is synonymous with the application of noble morals, therefore the aim of this research is to explain how Islamic Religious Education Teachers Efforts to Form Islamic Religious Akhlakul Karimah Based on Islamic Boarding Schools at MTs Darun Najah Karangploso, Malang Regency. This research method uses a qualitative approach with data collection procedures using observation, interviews and documentation as well as triangulation techniques to check the validity of the data. The results of the research state that Islamic Religious Education Teachers are a conscious effort to develop and nurture students, so that they can always understand the content of Islamic teachings as a whole, appreciate the purpose of food, which in the end can practice and make Islam a way of life. If seen from the meaning- In the above understanding, the role of the teacher is very important in the formation of a person’s morals in everyday life, especially in life starting in society. Teachers are very helpful in becoming representatives in forming the character of students in determining attitudes, ethics and behavior in accordance with religious guidance. Keywords: Keywords: Teacher Efforts, Education, Akhlakul Karimah.